Penurunan Kelelahan, Beban Kerja, Waktu Pengerjaan serta Peningkatan Hasil Belajar Menggunakan Pendekatan Ergonomi Total Dengan Sistem Diskusi dan Simulasi Video Dalam Meningkatkan Kompetensi pada Tindakan Pencabutan Gigi M1 RA - Sudirman, Putu Lestari; Anggayanti, Nyoman Ayu; Widari, I GAA Tirana Pramesti; Pradnyana, Made Yuda (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic); Vol 9 No 2 (2023): Volume 9 No 2 Tahun 2023, 2024)
Tooth extraction is an action that has a high prevalence in dental practice. The readiness of the operator in carrying out the extraction procedure has given positive impact to the patient, both in term of procedure and psychology of patient. Several studies have discussed related to the anxiety of the dentistry profession students in carrying out extraction procedures. This study aimed to prove whether the discussion and video simulation system before performing the extraction of the upper maxillary first molar can reduce fatigue, workload, working time, and increase the evaluation score of dentistry profession students. This research was conducted experimentally using a randomized pre-posttest control group design, with 32 dentistry profession students as the subject. Subjects were divided into two groups. The Control Group (CG) was given a discussion system with panthom simulation and the Intervention Group (IG) was given an intervention of discussion system with panthom and video simulation. Data analysis used Independent – Sample t-Test and U-Mann Whitney Test. The result of the analysis showed that there was a significant difference between CG and IG. General fatigue score CG = 20.06±1.82, IG = 14.22±3.69, CG workload = 26.07±2.40 beats/minute, IG = 21.10±1.82 beats/minute, CG working time = 55.06±9.48 minutes, IG = 41.67±5.89 minutes, CG evaluation score = 81.39±3.62, IG = 85.19±2.95 ( p<0.005 ) . It can be concluded that the application of a total ergonomics approach with discussion and video simulation of tooth extraction can reduce fatigue, workload, working time, and improve learning outcomes of dentistry profession students in the practice of extraction.